2018
DOI: 10.1016/j.copsyc.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The social neuroscience of race-based and status-based prejudice

Abstract: The largely independent neuroscience literatures on race and status show increasingly that both constructs shape how we evaluate others. Following an overview and comparison of both literatures, we suggest that apparent differences in the brain regions supporting race-based and status-based evaluations may tap into distinct components of a common evaluative network. For example, perceiver motivations and/or category cues (e.g., perceptual vs. knowledge-based) can differ depending on whether one is processing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 79 publications
3
31
0
Order By: Relevance
“…In our original univariate analyses ( Mattan et al, 2018a ), we found that EMS modulated responses to SES in the bilateral nucleus accumbens (NAcc) and ventromedial prefrontal cortex (VMPFC), consistent with the literature on status-based evaluations ( Mattan et al, 2017 , 2018b ). Notably, high-EMS participants showed neural response patterns to SES that were difficult to reconcile with the largely positive evaluations of high SES (when considered independently of other dimensions) observed in the behavioral ( Fiske, 2010 ; Varnum, 2013 ) and neuroimaging ( Mattan et al, 2017 , 2018b ) literature.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In our original univariate analyses ( Mattan et al, 2018a ), we found that EMS modulated responses to SES in the bilateral nucleus accumbens (NAcc) and ventromedial prefrontal cortex (VMPFC), consistent with the literature on status-based evaluations ( Mattan et al, 2017 , 2018b ). Notably, high-EMS participants showed neural response patterns to SES that were difficult to reconcile with the largely positive evaluations of high SES (when considered independently of other dimensions) observed in the behavioral ( Fiske, 2010 ; Varnum, 2013 ) and neuroimaging ( Mattan et al, 2017 , 2018b ) literature.…”
Section: Introductionsupporting
confidence: 85%
“…Previous neuroimaging work has implicated the frontal control network (including the ACC) in the regulation of prejudice in paradigms ranging from race-irrelevant spatial location tasks ( Richeson et al, 2003 ; Cunningham et al, 2004 ) to race-related fear learning ( Dunsmoor et al, 2016 ) and measures of implicit bias ( Beer et al, 2008 ; Fourie et al, 2014 ). In recent reviews, the ACC [i.e., dorsal ACC (dACC)] is typically considered to reflect monitoring for conflicts between internal desires to be egalitarian and an undesirable propensity for stereotypic or prejudiced responses ( Kubota et al, 2012 ; Amodio, 2014 ; Kubota and Ito, 2016 ; Mattan et al, 2018b ). It bears mentioning that cingulate activity in the present analysis was localized to the rACC and the MCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing neuroscientific evidence that people process information from ingroup and outgroup members in a different way (for reviews see: Ito and Bartholow, 2009 ; Cikara et al, 2011b ; Kubota et al, 2012 ; Eres and Molenberghs, 2013 ; Molenberghs, 2013 ; Amodio, 2014 ; Cikara and Van Bavel, 2014 ; Han, 2018 ; Mattan et al, 2018 ). Biases toward outgroup members affect perceptions, attitudes and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…And thus an understanding of neural mechanism is incomplete without an appreciation of its range of social function. Indeed, the neural processes underlying social perception, cognition, and emotion are modulated by group membership and status cues (Vollberg & Cikara, 2018;Mattan, Wei, Cloutier, & Kubota, 2018), and the brain is attuned to the structure social networks and the way information moves through them (Weaverdyck & Parkinson, 2018;Baek & Falk, 2018). Many aspects of social cognition, such as empathy, are no longer considered automatic processes that unfold with subject specific intensity, but rather processes that people selectively approach or avoid based on motivation in a social context (Weisz & Zaki, 2018).…”
mentioning
confidence: 99%